RELATIONSHIP OF THE IMMUNOLOGICAL PARAMETRES WITH NEOADJUVANT CHEMOTHERAPY EFFECTIVENESS IN BREAST CANCER PATIENTS - Y. V. Kukharev; M. N. Stakheeva; A. V. Doroshenko; N. V. Litvyakov; N. N. Babyshkina; E. M. Slonimskaya; N. V. Cherdyntseva (Сибирский онкологический журнал)
Experimental and clinical evidence suggests that the immune system when exposed to conventional cancer chemotherapy is involved in the antitumor effect. A study is conducted to assess the relationship between immunological parameters and effectiveness of neoadjuvant chemotherapy (NAC) in breast cancer (BC) patients. The study included 269 patients with BC (T1–4N0–3M0) and 24 practically healthy comparable age women. The estimation of the subpopulation composition of blood mononuclear cells, their functional activity, apoptosis markers, allelic polymorphism of cytokine genes, depending on the presence or absence of clinical response to NAC was done. Complete tumor regression was associated with an increase in the number of cytotoxic CD8+-cells, high functional activity of lymphocytes (proliferation in response to mitogen, the secretion of cytokines TNFα, IL-1β and IL-10, IFN-γ) and neutrophils. Close relation of highly functional cytokine genotype and high cytokine secretion in blood cells with an objective clinical response to chemotherapy was revealed. Thus, the findings suggest that an objective clinical response to NAC is associated with structural and functional preservation of the immune system. Constitutive characteristics of the patient’s organism, responsible for the level of expression of pathogenetically relevant cytokines that play a key role in the functioning of the immune system are have important meaning.